2022
DOI: 10.1038/s41467-022-30785-8
|View full text |Cite
|
Sign up to set email alerts
|

Cis- and trans-resveratrol have opposite effects on histone serine-ADP-ribosylation and tyrosine induced neurodegeneration

Abstract: Serum tyrosine levels increase during aging, neurocognitive, metabolic, and cardiovascular disorders. However, calorie restriction (CR) and sleep lower serum tyrosine levels. We previously showed that tyrosine inhibits tyrosyl-tRNA synthetase (TyrRS)-mediated activation of poly-ADP-ribose polymerase 1 (PARP1). Here, we show that histone serine-ADP-ribosylation is decreased in Alzheimer’s Disease (AD) brains, and increased tyrosine levels deplete TyrRS and cause neuronal DNA damage. However, dopamine and brain-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 82 publications
(152 reference statements)
0
12
0
Order By: Relevance
“…To circumvent this, we opted to apply R daily without disturbing the gauze patch from the treated area of mouse dorsal skin. The R concentration of 2.5 μg/mL was selected based on previous studies [ 2 , 9 ]. This concentration of R is considered moderate and physiologically relevant for in vivo studies as well [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To circumvent this, we opted to apply R daily without disturbing the gauze patch from the treated area of mouse dorsal skin. The R concentration of 2.5 μg/mL was selected based on previous studies [ 2 , 9 ]. This concentration of R is considered moderate and physiologically relevant for in vivo studies as well [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol (trans-3-4′,5-trihydroxystilbene, R) is an extensively studied natural polyphenolic phytoalexin enriched in red grapes that has gained attention for its overall anti-inflammatory effects [ 2 , 3 , 4 , 5 , 6 , 7 ]. However, animal studies and human clinical trials have yielded contrasting results with beneficial, lack of beneficial, or even adverse effects on health, owing to differences in experimental models, R bioavailability and pharmacokinetics [ 8 ], dosing [ 9 , 10 ], formulation, and circadian variation [ 2 ]. Additionally, R exerts contrasted effects depending on the prevalent stereoisomer present in solution [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lack of definite evidence, the role of resveratrol on the cerebral blood flow is important especially considering the vascular alterations found in most of the age-related diseases [ 176 ]. Interestingly, recent findings demonstrated that cis- and trans-resveratrol have the opposite effects on histone serine-ADP-ribosylation and tyrosine-induced neurodegeneration, so that the age-associated increase in serum tyrosine levels may affect neurocognitive and metabolic disorders, offering a plausible explanation for divergent results obtained in clinical trials using resveratrol [ 177 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Recently, tyrosine transfer-RNA synthetase (TyrRS), a member of the aminoacyl-tRNA synthetase (AARS) family, was reported to exert a neuroprotective effect on Alzheimer's disease (AD). 6 High expression of TyrRS significantly attenuated oxidative DNA damage in primary rat cortical neurons. 6 Moreover, TyrRS gene mutation was associated with the occurrence of the peripheral nerve degeneration diseases Charcot-Marie-Tooth and Leber hereditary optic neuropathy.…”
mentioning
confidence: 95%